Solving University Course Timetabling Problem (UCTP) Using Depth First Search (DFS) Algorithm and Rule Base Systems - ., Fatchurrochman; Abidin, Zainal (International Journal of Engineering and Technology, 2019)
University course timetabling are administrative activities undertaken by the universities to manage their resources for education process. The resources are classrooms and lecturers. In this research, the university course timetabling or course scheduling is seen as the search process. Searches conducted on unused slots to be filled with lectures classroom. slot is a term used to denote an entity that can be filled with classroom lectures. Lectures classroom are objects to be scheduled. DFS is used to prepare candidates for the class schedule of a lecture classroom. Subsequently checked whether the candidate's course schedule does not violate the lecturers constraint, classroom constraints, dhuhur prayer time constraint, Friday prayer time constraint, and in accordance with the preferences day of lecturer. If the candidate does not violate all constraint it will be stored as class schedules and if violated the constraint it will look for another schedules candidate. The system testing showed that of the 131 lectures classroom can all be scheduled at 6 classroom without breaking the constraints that have been set. There are 20 lectures classroom that are not scheduled when only 5 classroom used, this indicates that the DFS is not complete and is not optimal, this algorithm requires sufficient classrooms in order to work properly. In terms of computing time, this study provides the big picture of time required to complete the preparation of lecture schedules using DFS.Â Â